Reporting of the human rights to the environment of DHESCA platform: a new field of possibilities - Mello, Cecília Campello do Amaral; Lisboa, Marijane Vieira (FCL-UNESP Laboratório Editorial, 2013)
The national reporting project in human rights of the DhESCAPlatform, articulated by NGOs and social movements, despite the limited possibilities of direct intervention in the numerous situations of right violation in the country, has been working as an evidence trigger of the environmental injustice ambiance in Brazil. In the current article, as from contemporary political philosophy contributions, we propose an exercise of reflecting the activities of the environmental human rights reporting, to which we acted jointly between 2009 and 2011. At a first step, we proposed a discussion on the subject of the “evil alternatives” and limiting trigger of the policy, taken as emancipatory practice for a common world sharing; then we analyzed the importance of the disagreement stated as a democratic system assumption; subsequently, we discussed how it is built the reporter legitimacy action, and eventually we analyzed some effects of the Reporting, from concrete experiences to which we had access during our term.